GALANT, T. W. Risk and Survival in Ancient Greece. Reconstructing the Rural Domestic Economy. Cambridge: Polity Press, 1991. - Chevitarese, André Leonardo (Classica - Revista Brasileira de Estudos Clássicos, 1995)
.